Electronic Word of Mouth at Online Travel Agent Traveloka - Hutasoit, Suwindy; Zakiah, Siti (INTERACTION: Jurnal Pendidikan Bahasa, 2024)
This research aims to analyze positive e-WOM on Online Travel Agent Traveloka and negative e-WOM on Online Travel Agent Traveloka. This research type uses qualitative research carried out on Traveloka users who are in Bandung City and have made purchases at the Traveloka online travel agent. The sources of informants in this research are the OTA Traveloka user community and OTA Traveloka admins. Data collection techniques were carried out using observation, interviews, and documentation. To find out E-WOM at Online Travel Agent (OTA) Traveloka, researchers have distributed questionnaires to 6 respondents. The researchers use dimensions and indicators to measure E-WOM. In the intensity dimension, are 3 indicators used, including the frequency of accessing Traveloka user information, the frequency of interaction between Traveloka users, and the number of reviews written by Traveloka users. Positive E-WOM is essential in building a positive brand image and increasing user trust in Traveloka. Negative E-WOM can reduce the level of user trust in Traveloka. Negative reviews signal a problem or dissatisfaction with the service or product, affecting the overall perception of the platform's credibility.